2007
DOI: 10.1590/s0100-54052007000300013
|View full text |Cite
|
Sign up to set email alerts
|

Extratos de Lentinula edodes e Agaricus blazei sobre Bipolaris sorokiniana e Puccinia recondita f. sp. tritici, in vitro

Abstract: W i t h t h e p u r p o s e o f f i n d i n g a l t e r n a t i v e w a y s t o c o n t r o l Bipolaris sorokiniana and Puccinia recondita f. sp. triciti, the fungitoxic effect in vitro of Lentinula edodes and Agaricus blazei mushrooms was tested on these fungi. The aqueous crude extract of both mushrooms did not have significant effect on mycelial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
2
0
3
Order By: Relevance
“…tritici, embora não tenham apresentado efeito sobre o crescimento micelial e a germinação de esporos de Bipolaris sorokiniana (Sacc. In Sorok) Schoem (12).…”
Section: Resultsunclassified
“…tritici, embora não tenham apresentado efeito sobre o crescimento micelial e a germinação de esporos de Bipolaris sorokiniana (Sacc. In Sorok) Schoem (12).…”
Section: Resultsunclassified
“…This increase in lesioned area by the pathogen under these treatments can be related to the absence or low concentration of molecules with biological activity that can induce the activation of defense mechanisms in tomato plants; in addition, the sugar in the growth medium (batata and dextrose medium) affects saprobic fungi. High concentrations of proteins and carbohydrates in the filtrate composition could act as a nutritional source, favoring the pathogen growth, as described by Fiori-Tutida et al (2007), who found increases in mycelial growth and germination of Bipolaris sorakiniana treated with Lentinula edodes filtrate.…”
Section: Resultsmentioning
confidence: 80%
“…Além destes, adotou-se os tratamentos padrões utilizados como controle: calda bordalesa na proporção 1:1:100 (sulfato de cobre:cal virgem:água v:v:v) e mancozebe a 2,5 g p.c. L -1 (Manzate® 800, Dow AgroSceinces Industrial LTDA), e os tratamentos alternativos: acibenzolar-S-methyl a 0,05 g p.c L -1 (Bion®, Syngenta Proteção de Cultivos LTDA) e Agaricus blazei (1 g de pó seco para 14 mL de água) (FIORI-TUTIDA et al, 2007).…”
Section: Aplicações Em Pré E Pós-colheitaunclassified